USING PARTIAL DIFFERENTIAL EQUATIONS FOR PRICING OF GOODS AND SERVICES - TRAYKOV, Metodi; TRENCHEVA, Miglena; MAVREVSKI, Radoslav; STOILOV, Anton; TRENCHEV, Ivan (Scientific Annals of Economics and Business, 2016)
This article is based on the methodology of comparative analysis, using an innovative approach for pricing of various goods and services. Benchmarking is the continuous search to find and adapt better pricing methods that leading to increased profits. We will consider the numerical solution of partial differential equations, based on Black-Scholes model for pricing of goods and services within European option. Also, we will present formulation and numerical behavior of explicit and implicit methods that can be use in pricing for company assets within European option. JEL Codes - Y80